2010
DOI: 10.3390/ijms11124782
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Photoaging Effects of Soy Isoflavone Extract (Aglycone and Acetylglucoside Form) from Soybean Cake

Abstract: Soy isoflavones, found in soybean and soybean products, have been reported to possess many physiological activities such as antioxidant activity, inhibition of cancer cell proliferation, reduction of cardiovascular risk, prevention of osteoporosis and alleviation of postmenopausal syndrome. In our previous study, soy isoflavone extract ISO-1 (containing 12 soy isoflavones) from soybean cake was demonstrated to prevent skin damage caused by UVB exposure. In this study, soy isoflavone extract from soybean cake w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…The anti-inflammation of melanogenesis was observed in mouse models [9, 28]. UVB exposure (150 mJ/cm 2 ) led to ICR-Foxn/ nu mice dorsal skin erythema, desquamation, and transdermal water loss.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammation of melanogenesis was observed in mouse models [9, 28]. UVB exposure (150 mJ/cm 2 ) led to ICR-Foxn/ nu mice dorsal skin erythema, desquamation, and transdermal water loss.…”
Section: Discussionmentioning
confidence: 99%
“…We found that FME exhibited good elastase inhibiting activity, inhibited MMP-1, -3, and -9 expression, and elevated type I procollagen production. Studies have shown that genistin inhibits UV-induced DNA damage in human melanoma cells and that isoflavones in soybean extract inhibit UVB-induced ROS, JNK activation, cyclooxygenase-2 activation, and proliferation of cell nuclear antigen in keratinocytes [28, 29]. FME, which is rich in the isoflavones genistin, genistein, and daidzin that are found in soybean and other natural products, might contribute to the antiphotoaging activity of FME.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2010) showed that the epidermal thickness of hairless mice was increased by UVB irradiation, but the extract of two test herbal compounds applied to the exposed skin reduced the epidermal thickness. Also, topical application of the isofl avone extract from soybean cake before UVB irradiation decreased the epidermal thickness (Huang et al 2010). Orally administered olive leaf extract and oleuropein prevented increased skin thickness and reduction of skin elasticity by preventing increased expression of matrix metalloproteinases (MMP-2, 9 and 13) in UVB irradiated hairless mice .…”
Section: Fig 1 O Hypericifolium Oil In Uvb Non-irradiated (Group 3mentioning
confidence: 99%